Dilated Cardiomyopathy due To Coxsackie-B Virus Myocarditis: A Case Report - Begum, Nurun Nahar Fatema; Hossain, Md Rabiul; Sarker, Md Ferdousur Rahman (Journal of Armed Forces Medical College, Bangladesh, 2017)
Dilated cardiomyopathy (DCM) is a rare disorder which may be caused by diverse reasons. Many of them are idiopathic also. The article reports a case of DCM resulting from acute Coxsackie virus myocarditis. Antibody to Coxsackie-B virus was positive from a lab of United States of America. This is first case report of Coxsackie-B virus myocarditis (proven) led to cardiomyopathy in Bangladesh. Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 131-133